Tocqueville : the aristocratic sources of liberty - Jaume, Lucien (Princeton University Press, 2013)
Many American readers like to regard Alexis de Tocqueville as an honorary American and democrat--as the young French aristocrat who came to early America and, enthralled by what he saw, proceeded to write an American book explaining democratic America to itself. Yet, as Lucien Jaume argues in this acclaimed intellectual biography, Democracy in America is best understood as a French book, written primarily for the French, and overwhelmingly concerned with France. "America, " Jaume says, "was merely a pretext for studying modern society and the woes of France."